Sculptural textile art : a practical guide to mixed media wire sculpture - Edwards, Priscilla (Textile artist., 2022)
Priscilla's contemporary mixed media artworks offer a refreshingly different approach to embroidery, taking stitch to an impressive new level within wire sculpture. Working both two- and three-dimensionally, she combines color, stitch, shape and texture, layering and transforming surfaces into beautiful, whimsical sculptures full of character, curiosity and charm. With her imaginative use of the needle and her love of retro vintage nostalgia, Priscilla has picked up on an enduring trend, exploring excitingly different ideas and pushing the boundaries with her original ways of working.